A Fixed Point Approach to the Stability of an n-Dimensional Mixed-Type Additive and Quadratic Functional Equation - Yang-Hi Lee; Soon-Mo Jung (Abstract and Applied Analysis)
We investigate the stability problems for a functional equation 2f(∑j=1nxj)+∑1≤i,j≤n,  i≠jf(xi-xj)=(n+1)∑j=1nf(xj)+(n-1)∑j=1nf(-xj) by using the fixed point method.